2018
DOI: 10.3389/fpsyt.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Emotional Faces in Patients with Chronic Pain Disorder: An Eye-Tracking Study

Abstract: ObjectiveProblems in emotion processing potentially contribute to the development and maintenance of chronic pain. Theories focusing on attentional processing have suggested that dysfunctional attention deployment toward emotional information, i.e., attentional biases for negative emotions, might entail one potential developmental and/or maintenance factor of chronic pain.MethodsWe assessed self-reported alexithymia, attentional orienting to and maintenance on emotional stimuli using eye tracking in 17 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Independent of group (patients vs. controls), we found that (1) emotional faces attracted more attention than neutral faces, and (2) happy faces were attentionally preferred over angry and pain faces in the later stages of processing. These findings are in line with the results of our previous study [ 16 ] and with several other eye tracking studies either reporting attentional preference for emotional stimuli in general (emotionality bias) [ 8 , 9 , 12 , 14 ] or attentional preference for happy faces (positivity bias) [ 10 , 29 ] in both pain patients and controls.…”
Section: Discussionsupporting
confidence: 93%
“…Independent of group (patients vs. controls), we found that (1) emotional faces attracted more attention than neutral faces, and (2) happy faces were attentionally preferred over angry and pain faces in the later stages of processing. These findings are in line with the results of our previous study [ 16 ] and with several other eye tracking studies either reporting attentional preference for emotional stimuli in general (emotionality bias) [ 8 , 9 , 12 , 14 ] or attentional preference for happy faces (positivity bias) [ 10 , 29 ] in both pain patients and controls.…”
Section: Discussionsupporting
confidence: 93%
“…While they found differences in biases towards emotional stimuli (including happy faces) between the participants with and without chronic pain in the control group where depression differed, no such differences were observed between the participants with and without chronic pain where both groups were matched on depression. Unfortunately, Giel et al 57 did not include pain faces in their study and therefore whether similar levels of depression could account for the current findings remains speculative.…”
Section: Discussionmentioning
confidence: 76%
“…On the contrary, it may be that anxiety, stress, and depression are important to attentional processes and that biases towards pain are ONLY observed in samples that differ on key measures of distress. For example, Giel et al 57 assessed the ABs of participants with chronic pain and two control groups, one of whom were matched for depressive symptoms. While they found differences in biases towards emotional stimuli (including happy faces) between the participants with and without chronic pain in the control group where depression differed, no such differences were observed between the participants with and without chronic pain where both groups were matched on depression.…”
Section: Discussionmentioning
confidence: 99%
“…In free-viewing tasks, participants were typically asked to freely explore one (Schoth, Wu, et al, 2019) or more (Priebe et al, 2015) visual stimuli simultaneously presented in random locations as if they were watching television. In some studies, participants were informed about locations in which emotional stimuli (i.e., happy or sad face) would appear prior to free-viewing (Giel et al, 2018). In others, free-viewing of certain visual stimuli was followed by possible pain stimulation versus its absence (Jackson et al, 2018a(Jackson et al, , 2018b.…”
Section: Pain and Eye-tracking Measures Of Attentional Biasesmentioning
confidence: 99%